Optimizing Employee Performance through Work Motivation and Job Satisfaction: A Case Study in a Surabaya-based Company - Irfan, Mochamad; Sigita, Dwi Sembe; Hariani, Mila (Bulletin of Science, Technology and Society, 2023)
This study examines the relationship between work motivation, job satisfaction, and employee performance in a company in Surabaya. The problem faced by the company is related to the low quality of human resources, which is an important asset and must be managed properly to provide an optimal contribution. This study aims to determine the role of work motivation on employee performance through job satisfaction. In this research method, the focus is on analyzing the effect of work motivation on employee performance, with job satisfaction as an intervening variable. The research population is all employees of the company, with a total of 84 respondents. The results of the analysis show that work motivation has a positive and significant influence on employee performance, and job satisfaction acts as an intermediate variable in the relationship.